Serum angiotensin converting enzyme in pemphigus vulgaris - Reza M Robati; Azin Ayatollahi; Parviz Toossi; Shima Younespour (Wolters Kluwer Medknow Publications, 2014)
Background: Pemphigus vulgaris is an autoimmune blistering skin disease with unknown etiology. Drugs such as angiotensin-converting enzyme (ACE) inhibitors may contribute in the pathogenesis of pemphigus. Objective: We plan this essay to evaluate the serum ACE level in pemphigus vulgaris patients in comparison with healthy controls to recognize its possible role in disease pathogenesis or activity. Methods: This study was planned and performed in the dermatology clinics of Shahid Beheshti University of MedicalSciences' Hospitals between July 2010 and June 2011. Patients with new onset of pemphigus vulgaris were enrolled in our study. Control subjects were frequency-matched to cases by sex and age. Serum ACE was determined by the spectrophotometric method. Results: Thirty-four patients with pemphigus vulgaris and 35 healthy individuals were recruited in the study. No statistical significant difference was detected in the mean level of serum ACE of the two groups (t-test, P = 0.11). The mean ACE level was significantly lower in male patients compared with male controls (P = 0.04). Moreover, a significant higher serum ACE level of patients with cutaneous involvement was observed compared to patients with mucosal involvement (P = 0.02). Conclusions: Despite lack of any significant difference of serum ACE level between pemphigus and control group, the serum ACE level was considerably lower in male pemphigus vulgaris patients compared with male controls. Therefore, ACE might have some association with pemphigus vulgaris especially in male patients; however, further studies are required to confirm this association.